THE EFFECT OF PRICE AND PRODUCT QUALITY ON TELKOMSEL USER LOYALTY - Zikriatul Ulya (JIM: Jurnal Ilmiah Mahasiswa, 2022)
Increasing consumer demand for telecommunications products that provide information and communication services. Consumers demand better service and are personally involved in developing a product. so that telecommunications companies compete to get consumers and retain consumers. This study aims to determine how the influence of price and product quality variables on the loyalty of Telkomsel users. The population in this study are Telkomsel users in Langsa City. The sampling technique used is accidental sampling with a sample of 100 respondents. Methods of data collection using a questionnaire. The method of data analysis is multiple linear regression using SPSS. The results of this study indicate that the variables of Price and Product Quality simultaneously have a positive and significant effect on Telkomsel User Loyalty. Partially, the Price variable has a positive and significant effect on Telkomsel User Loyalty and the Product Quality variable has a positive and significant effect on Telkomsel User Loyalty. The results of this test result in the coefficient of determination (adjusted R2) obtained at 0.529 or 52.9%, meaning that the variable user loyalty is influenced by the price and product quality variables. the remaining 47.1% is explained by other variables.